Methods used by mathematics teachers in developing parallel multiple-choice test items in school - Kartika Pramudita; R. Rosnawati; Socheath Mam (REID (Research and Evaluation in Education), 2019)
The study was aimed at describing five methods of the development of parallel test items of the multiple-choice type in mathematics at Yogyakarta (primary education level). The study was descriptive research involving 22 mathematics teachers as the respondents. Data collection was conducted through interviews and document reviews concerning the developed test packages. A questionnaire was used to gather data about the procedure the teachers employed in developing the tests. Findings show that the teachers used five methods in developing the test item; namely (1) randomizing the item numbers; (2) randomizing the sequences of response options; (3) writing items using the same contexts but different figures; (4) using anchor items; and (5) writing different items based on the same specification table. All of the respondents stated that they developed the table of the specification before developing the test items and that most of them (77%) did the validation of the instruments in content and language.